Reading Success in the Primary Years An Evidence-Based Interdisciplinary Approach to Guide Assessment and Intervention - Westerveld, Marleen F.; Armstrong, Rebecca M.; Barton, Georgina M. (Springer Nature Singapore : Imprint: Springer, 2020)
This open access book describes the Reading Success project, in which a 5-step, assessment-to- intervention process, based on the Simple View of Reading, was used within a primary school setting in Australia to better support those students who struggle with reading. It provides an easily accessible overview of each step of the process involved in implementing this approach and highlights the crucial importance of collaboration between professionals involved in the teaching of reading within a school setting. It focuses on the decision-making processes used, such as rich dialogue with the leadership team and teachers, and shares participants' perspectives gathered throughout the project. Using case studies, the book describes how the 5-step approach assists in creating detailed profiles of students' strengths and weaknesses in spoken and written language skills that can be used to guide targeted intervention This book offers valuable insights for educators, speech pathologists, researchers, and pre-service teacher education students interested in the teaching of reading.